2021
DOI: 10.32584/jkmk.v4i2.1230
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Fungsi Manajemen Kepala Ruangan dengan Pelibatan Pasien (Patient Engagement) dalam Asuhan Keperawatan di Masa Pandemi Covid-19

Abstract: Rumah sakit harus menetapkan regulasi dan proses untuk mendukung pelibatan pasien dalam proses asuhan sebagai upaya memfasilitasi keterlibatan pasien secara aktif. Adanya  keterbatasan interaksi antara perawat dan pasien secara aktif menjadi sebuah tantangan tersendiri di masa pandemi Covid-19. Penelitian ini bertujuan mengetahui hubungan fungsi manajemen kepala ruangan dengan pelibatan pasien dalam asuhan keperawatan di masa pandemi Covid-19. Penelitian ini menggunakan desain penelitian cross sectional terhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…In research conducted by Ilham & Suharto (2022), the results showed that 64.7% of respondents said they felt satisfied at the orientation stage, 66.3% felt satisfied at the work stage, and 69.5% felt satisfied at the termination stage, meaning that 95 respondents said satisfaction with nurses' therapeutic communication services during the pandemic. According to Fauziyah et al (2022) from research on the relationship between nurses' skills with 238 respondents, the average result of nurses' communication skills was 62.07% of the maximum result with the highest score for nurses on the item paying attention to patients with a result of 68.18% of the maximum value. According to Suhendi & Yuliani (2022), family meetings conducted by the patient care manager (MPP) with the patient's family result in the MPP as a facilitator is essential for patients so that they do not feel physically isolated and the family does not feel anxiety, reduces complaints and increases satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…In research conducted by Ilham & Suharto (2022), the results showed that 64.7% of respondents said they felt satisfied at the orientation stage, 66.3% felt satisfied at the work stage, and 69.5% felt satisfied at the termination stage, meaning that 95 respondents said satisfaction with nurses' therapeutic communication services during the pandemic. According to Fauziyah et al (2022) from research on the relationship between nurses' skills with 238 respondents, the average result of nurses' communication skills was 62.07% of the maximum result with the highest score for nurses on the item paying attention to patients with a result of 68.18% of the maximum value. According to Suhendi & Yuliani (2022), family meetings conducted by the patient care manager (MPP) with the patient's family result in the MPP as a facilitator is essential for patients so that they do not feel physically isolated and the family does not feel anxiety, reduces complaints and increases satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Hospitals must have regulations that support patient involvement in the educational process. The role of nurse educators is vital here, as they must facilitate active patient involvement 16. In addition, the head nurse role has a significant relationship with both management functions concerning patient education (planning, organizing, staffing, directing, and supervising) and patient involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nurse educators is vital here, as they must facilitate active patient involvement. 16 In addition, the head nurse role has a significant relationship with both management functions concerning patient education (planning, organizing, staffing, directing, and supervising) and patient involvement. Excellent nurse educators will always strive to ensure the understanding of patients and their families by modifying the education provided, checking on knowledge levels, and using appropriate tools to change patients' attitudes and behaviors.…”
Section: Theme 4 Being Aware Of the Rolementioning
confidence: 99%
“…Perawatan yang berfokus pada pasien atau biasa disebut patient centered care (PCC) merupakan suatu keharusan bagi profesional pemberi asuhan dalam melaksanakan pelayanannya. Dalam proses perawatan, pendekatan ini secara aktif menghormati dan responsif terhadap nilai, kebutuhan, serta preferensi pasien dalam perencanaan, proses maupun evaluasi perawatan (Fauziyah, 2021). PCC mampu mendorong kolaborasi aktif antara pasien/keluarga dengan profesional pemberi layanan untuk memperoleh keputusan bersama dalam merancang dan mengelola rencana perawatan pasien (Pilnick, 2022).…”
Section: Pendahuluanunclassified